Spiritualising Communication Technology The Use of New Media for Da’wah Purpose Among USIM Communication Students - Sofia Hayati Yusoff; Fauziah Hassan; Amirah Zainun (USIM Press, 2024)
Vol. 23 No. 2 (2020): Journal of Islamic Social Sciences and Humanities (Special Issue)